The Influence of Social Support on the Interpersonal Intelligence of Sriwijaya State Buddhist College Students - Yanti, Erika; Amiro, Tri; Muawanah, Muawanah; Asdar, Ahsanul Khair; Karbono, Kemanya (LPPM Universitas Negeri Jakarta, 2025)
Interpersonal intelligence is the understanding of the feelings, wants, and intentions of other people in day-to-day activities. Interpersonal intelligence facilitates the completion of tasks and responsibilities because students with interpersonal intelligence possess social sensitivity, social insight, and social communication which helps students become more responsible. The development of interpersonal intelligence also involves many factors, one of which is social support. Social support given from different people can foster the development of students’ interpersonal intelligence. The research was aimed to find out the effect of social support on the interpersonal intelligence of STABN Sriwijaya students using the questionnaire/survey method. The respondents in this research were 91 active students. The results of the prerequisite test indicated that the data were normally distributed, the effect of the independent variable on the dependent variable was linear and there was no autocorrelation. Social support and the interpersonal intelligence of students were found to have a very strong relationship. Social support contributed 14.6% to the development of interpersonal intelligence in students.